My reflections on the 2024– 2025 South African Heart® Journal year - Meel, Prof Ruchika (SA Heart Journal, 2025)
The 2024–2025 editorial year in review for the SA Heart® Journal reflects a dynamic and impactful year in cardiovascular research and clinical practice. Following a brief pause during 2023–2024, the journal successfully returned to regular publication with 4 consecutive issues. Each edition was anchored around key themes: the congress issue (Cardiology Connections), valvular heart disease, coronary artery disease, heart failure, and training and research. Educational features, such as the electrocardiography quiz and cardiac imaging quiz, remained integral, continuing to enhance clinical learning and engagement.